Profil Keterampilan Berpikir Tingkat Tinggi Siswa SMP dalam Menyelesaikan Soal AKM Konten Aljabar Ditinjau dari Gaya Kognitif - Grisa Fima Nurandika; Rooselyna Ekawati (MATHEdunesa, 2023)
Higher-order thinking skills (HOTS) are vital skills that must be possessed. HOTS is a cognitive process that includes the levels of analyze (C4), evaluate (C5), and create (C6). The government's effort to improve HOTS is by promoting AKM. One of the factors that affect thinking skills is cognitive style. In mathematics, abstract ideas are often represented in the form of visual and verbal symbols. A Cognitive style that is associated with differences in visual and verbal reception of information is known as the visualizer-verbalizer cognitive style. This study is descriptive-qualitative research that aims to describe the profile of higher-order thinking skills of JHS students in solving AKM problems algebra content in terms of visualizer and verbalizer's cognitive style. The subjects of this study consisted of 2 students of grade IX with each visualizer and verbalizer student who had equal mathematical ability and the same gender. Research data collection techniques with AGK, AKM question tests, and interviews. Results of this study show that HOTS of visualizer at the analyze stage (C4) can identify any information that connected to solve the problem by first imagining the picture of the problem. At the evaluate stage (C5), carry out the process of checking and critiquing to make decisions. And at the create stage (C6), can make a hypothesis based on the result imagined in mind, then make a plan and implement it to obtain results. While verbalizer at the analyze stage (C4) can identify the information presented in the text that connected to solve the problem but less accurate in reading graphs. At the evaluate stage (C5), doesn't check the examination process but immediately makes a decision. And at the create stage (C6), can make a hypothesis based on their thinking then make a plan and implement it to obtain results that match with criteria.